VICTORIAN LITERATURE AND SOCIAL CHANGE: THE REFLECTION OF SOCIETY IN DICKENS’S WORKS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study examines the intersection of Victorian literature and social transformation, with a particular focus on the works of Charles Dickens. His novels provide a vivid portrayal of nineteenth-century English society, addressing issues such as industrial growth, urban expansion, poverty, social inequality, and the hardships faced by the working class. Through detailed character development, complex narrative structures, and pointed social commentary, Dickens not only represented the realities of his era but also sought to influence public awareness and encourage social reform. By analyzing selected works, including Oliver Twist, David Copperfield, and Hard Times, this paper highlights how Dickens’s literature functions as both a reflection of